Kid's visual reference of the United States - Blackbirch Press (San Diego, Calif. : Blackbirch Press, 2002)
An alphabetical presentation of brief statistics and pictorial information about each of the United States, as well as U.S. territories and possessions.
"More than 2,500 graphs, charts, maps, and photos that cover the most important and interesting facts about every state in our country!"
Keywords: U.S. states -- Miscellanea; U.S. states -- Pictorial works; United States -- Miscellanea; United States -- Pictorial works